2007
DOI: 10.1002/cjce.5450850206
|View full text |Cite
|
Sign up to set email alerts
|

Melt‐Phase Nylon 612 Polycondensation Kinetics: Effects of Sodium Hypophosphite Catalyst

Abstract: You et al., 1994). This study examines the catalytic effect of sodium hypophosphite (SHP). SHP is added to polyamides because, in addition to its catalytic properties, SHP acts as a whitening agent (Lysek and Ables, 2001), as well as a thermal stabilizer and antioxidant (Agouri and Muller, 1968;Kelmchuk, 1972;Kazuhiko et al., 1995), which gives desirable end-use properties to nylon fi bres and moulded products.SHP catalyzes a variety of esterifi cation and amidation reactions. For example, Fourier Transform In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…As shown in Table 7 , they used these data to estimate 20 kinetic parameters (including 10 activation energies) and 10 equilibrium parameters (including 5 reaction enthalpies). Parameter values estimated by other research groups (using smaller data sets or unpublished data) are also shown in Table 7 11,14–16,18,24,25,32,35,42,45–547 are similar for different research groups (e.g., the activation energy estimate of 78.7 kJ mol −1 for R1 reported by Arai et al11 is similar to 78.5 kJ mol −1 reported by Reimschussel et al,45 other parameter estimates differ by orders of magnitude between research groups.…”
Section: Reaction Mechanism and Literature Reviewsupporting
confidence: 62%
See 4 more Smart Citations
“…As shown in Table 7 , they used these data to estimate 20 kinetic parameters (including 10 activation energies) and 10 equilibrium parameters (including 5 reaction enthalpies). Parameter values estimated by other research groups (using smaller data sets or unpublished data) are also shown in Table 7 11,14–16,18,24,25,32,35,42,45–547 are similar for different research groups (e.g., the activation energy estimate of 78.7 kJ mol −1 for R1 reported by Arai et al11 is similar to 78.5 kJ mol −1 reported by Reimschussel et al,45 other parameter estimates differ by orders of magnitude between research groups.…”
Section: Reaction Mechanism and Literature Reviewsupporting
confidence: 62%
“…Parameter values from both Step 1 and Step 2 result in overprediction of the rate of polycondensation at high [ W ] (i.e., for experiments with initial water ≥3.5 wt%) and to underpredict the rate of polycondensation at low [ W ] (e.g., for experiments with initial water ≤1.18 wt%). This result is not particularly surprising because many authors have commented on the complex influence of water on polycondensation equilibrium and reaction rates 14–28. In our previous reaction equilibrium modeling study,28 side reactions involving amidine ends, cyclopentanone ends, and hydrated carboxyl ends (R7–R12 in Table 5) were used to develop a model for the complex behavior of K 2 a , which changes with [ W ] and T .…”
Section: Model Extension and Parameter Estimationmentioning
confidence: 91%
See 3 more Smart Citations